Temperature Correction of Deflections and Backcalculated Elasticity Moduli Determined from Falling Weight Deflectometer Measurements on Asphalt Pavements - Brezina, Ilja; Machel, Ondrej; Zavrel, Tomas (Communications - Scientific Letters of the University of Zilina, 2022)
The evaluation of the bearing capacity of asphalt pavements is usually performed by analysing the deflections measured by a Falling Weight Deflectometer (FWD). The deflection changes with the pavement temperature. In evaluation is necessary to consider the thermal gradient of pavement and perform the temperature correction. The article contains an analysis of effects of the pavement temperature on FWD results on the long-term monitored sections. The temperature correction was performed on measured deflections or back-calculated elasticity moduli. The moduli recalculated to the temperature of 20 °C according to both procedures were similar. Comparison of moduli determined by recalculation to moduli back-calculated from the deflection bowls measured at the temperature of 20 °C, has proven smaller differences for the moduli determined from the deflection bowl corrected to the temperature of 20 °C.
Keywords: asphalt pavement; elasticity modulus; deflection; deflectometer (FWD); temperature correction